2019
DOI: 10.1016/j.diabres.2019.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake in type 1 diabetes at different stages of diabetic kidney disease

Abstract: Diet plays an important role in the kidney health of individuals with type 1 diabetes. However, not much is known about dietary practices at different stages of diabetic nephropathy. We aimed at investigating food intake, dietary patterns, and nutrient intakes in individuals with type 1 diabetes differing in renal status. Methods: Data were available from 1874 individuals with type 1 diabetes (45% men, age 48 ± 13 years). Diet was assessed at the levels of food items and diet patterns (diet questionnaire), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The Guidelines indicate that protein intake should constitute about 15-20% of total calories, without details concerning sources. In our analysis, these values were within the normal limits; the reduction of intake of protein is recommended in the case of chronic kidney disease [37]. The sodium intake was above the recommended range, 126.6% (98.0%-154.4%) vs. 155.4% (116.2%-208.2%), p=0.05 (0.0458) (Table 4).…”
Section: Discussionsupporting
confidence: 54%
“…The Guidelines indicate that protein intake should constitute about 15-20% of total calories, without details concerning sources. In our analysis, these values were within the normal limits; the reduction of intake of protein is recommended in the case of chronic kidney disease [37]. The sodium intake was above the recommended range, 126.6% (98.0%-154.4%) vs. 155.4% (116.2%-208.2%), p=0.05 (0.0458) (Table 4).…”
Section: Discussionsupporting
confidence: 54%
“…This triggers intense hunger and leads to food intake increase in T1D patients or T1D model. [ 30 ] Meanwhile, excessive glycosuria can cause water loss, which leads to an increase in water intake. [ 31 ] In this study, it was found that rLZ‐8 could mitigate body weight loss and reduce the food and water intake of diabetic rats, suggesting that rLZ‐8 improve the quality of life in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have also examined dietary patterns specifically across different kidney function strata. We have shown that already early in diabetic kidney disease, with estimated glomerular filtration rate (eGFR) only mildly reduced (60-89 ml/min/1.73m 2 ), differences in eating patterns exist in type 1 diabetes ( 54 ). The general conclusion from our analysis was, that there is an overall trend towards healthier food choices upon advancing kidney disease, limiting salt intake and sweet food items ( 54 ).…”
Section: Nutrition - Meeting Diet Recommendations Glycemic Control An...mentioning
confidence: 99%
“…We have shown that already early in diabetic kidney disease, with estimated glomerular filtration rate (eGFR) only mildly reduced (60-89 ml/min/1.73m 2 ), differences in eating patterns exist in type 1 diabetes ( 54 ). The general conclusion from our analysis was, that there is an overall trend towards healthier food choices upon advancing kidney disease, limiting salt intake and sweet food items ( 54 ). Importantly, caloric intake was significantly reduced already with mildly reduced glomerular filtration rate and although the average BMI was not in the range of obesity (≤27 kg/m 2 , in all eGFR groups).…”
Section: Nutrition - Meeting Diet Recommendations Glycemic Control An...mentioning
confidence: 99%